Effects of NaCl stress on accumulation of K+, Na+, Cl-, NO3 -,sugar and proline contents in the seedlings of Triticale-I - Samad, Rifat; Karmoker, JL (Bangladesh Journal of Botany, 2014)
NaCl stress at 50 - 150 mM NaCl caused a 12 - 16-fold increase in Na+ accumulation in the root and 3 - 10-fold in the shoot of Triticale-I with a concomitant decrease in that of K+ and Cl- . NaCl stress increased the accumulation of reducing, total sugars and proline both in the root and shoot of the seedlings. The mechanism of salt tolerance of Triticale-I plants with respect to ionic relation and accumulation of sugars and proline were discussed. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18019 Bangladesh J. Bot. 42(2): 189-194, 2013 (December)